Context-free grammars to detect straight segments and a novel polygonal approximation method - Tapia-Dueñas, Osvaldo A.; Sánchez-Cruz, Hermilo (Signal processing. Image communication, 2021)
A new method for the polygonal approximation is presented. The method is based on the search for break points through a context-free grammar, that accepts digital straight segments with loss of information, as well as the decrease in the error committed employing the comparison of a tolerable error. We present an application of our method to different sets of objects widely used, as well as a comparison of our results with the best results reported in the literature, proving that our method achieves better values of error criteria. Besides, a new way to find polygonal approximations, with context-free grammars to recognize digital straight segments without loss of pixels, it is also addressed. •Break points through a context-free grammar in contour shapes are obtained.•An elimination of break points through an imposition of tolerable error is achieved.•Through an inspection of the updated breakpoints vicinity, a base-graph problem is modeled.•Computing the Dijkstra algorithm in the graphical problem allows obtaining the final dominant points.•Digital straight segments without pixel loss is also computed.